2018
DOI: 10.1371/journal.pone.0201733
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of HIV-associated pneumocystis pneumonia at a South African referral hospital

Abstract: HIV-associated pneumocystis pneumonia (PCP) is increasingly recognized as an important cause of severe respiratory illness in sub-Saharan Africa. Outcomes of HIV-infected patients with PCP, especially those requiring intensive care unit (ICU) admission, have not been adequately studied in sub-Saharan Africa. The aim of this study was to describe the clinical phenotype and outcomes of HIV-associated PCP in a group of hospitalized South African patients, and to identify predictors of mortality. We conducted a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…A recent systematic review found a prevalence of over 20% amongst inpatients presenting with respiratory symptoms in sub-Saharan Africa [17]. Outcomes are poor in these settings, with a pooled case fatality of 15% [17], reaching 60% in those admitted to ICU at one centre [18]. Improved diagnostics and treatment strategies are needed to improve patient prognosis in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found a prevalence of over 20% amongst inpatients presenting with respiratory symptoms in sub-Saharan Africa [17]. Outcomes are poor in these settings, with a pooled case fatality of 15% [17], reaching 60% in those admitted to ICU at one centre [18]. Improved diagnostics and treatment strategies are needed to improve patient prognosis in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…A study using the PaO 2 /FiO 2 ratio was also conducted by Chiliza et al in which the subjects were HIV patients with PCP infection. In this study, the PaO 2 /FiO 2 ratio was considered as a significant predictor of mortality (HR 3.8; 95% CI 1.68.9; p = 0.0030) [19]. Likewise, the similar result was also found in a study conducted by Wu et al, in which PaO 2 <70 as one of the mortality predictors had an HR of 7.328 (95% CI 3.621-14.830) on HIV/AIDS patients' mortality [20].…”
Section: Discussionmentioning
confidence: 87%
“…PCP prevalence is estimated to be >20% among HIV‐infected patients presenting with respiratory symptoms 68,69 . These studies have also indicated that outcomes are poor in Sub‐Saharan Africa, with case fatalities reaching up to 60% in those admitted to intensive care units in Cape Town, South Africa 70 . Therefore, PCP contributes substantially to the burden of disease in countries with high rates of HIV, which also face major challenges with diagnosis and treatment.…”
Section: Pneumocystis Jiroveciimentioning
confidence: 99%